2017
DOI: 10.3892/br.2017.867
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells to hepatocytes, the journey so far

Abstract: Abstract. Over the past several years, there has been substantial progress in the field of regenerative medicine, which has enabled new possibilities for research and clinical application. For example, there are ongoing efforts directed at generating functional hepatocytes from adult-derived pluripotent cells for toxicity screening, generating disease models or, in the longer term, for the treatment of liver failure. In the present review, the authors summarise recent developments in regenerative medicine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 67 publications
(54 reference statements)
1
38
0
Order By: Relevance
“…With the aim of replicating liver development in vitro, several groups have succeeded in differentiating human iPSCs into hepatocyte-like cells following a stepwise differentiation protocol based on several chemical inhibitors 63. An alternative approach was pursued by the Suzuki and Hui labs, which forced the expression of pioneer liver transcription factors ( HNF4a and FOXA1,2,3 )64 or ( HNF4a , GATA4 and HNF1B )65 to induce the direct differentiation of iPSCs into hepatocyte-like cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of replicating liver development in vitro, several groups have succeeded in differentiating human iPSCs into hepatocyte-like cells following a stepwise differentiation protocol based on several chemical inhibitors 63. An alternative approach was pursued by the Suzuki and Hui labs, which forced the expression of pioneer liver transcription factors ( HNF4a and FOXA1,2,3 )64 or ( HNF4a , GATA4 and HNF1B )65 to induce the direct differentiation of iPSCs into hepatocyte-like cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…We differentiated hiPSCs (human induced pluripotent stem cells) over 25 days ( 18, 19 ) into hepatocytes lineage during which the hepatoblast-to-hepatocyte differentiation took 6 days in vitro ( 20 ). During this hepatic lineage induction, we observed a mixed population of cells at different maturation stages ( 21 ). To assess hepatocyte maturity, we used the expression levels and localization of a small organic anion transporter MRP2 (Multidrug resistance-associated protein 2).…”
Section: Resultsmentioning
confidence: 95%
“…Hepatocyte-like cells derived from iPS cells (iPS-Heps) exhibit properties of hepatocytes, such as albumin secretion and metabolic functional properties. Several pathophysiological disorders can be reproduced using human iPS-Heps; on the contrary, the phenotypes of iPS-Heps are immature compared with adult mature hepatocytes with respect to albumin production, cytochrome P450 (CYP) activity and metabolic functions [18,19]. Recent reports have shown that patientderived iPS-Heps have been used to investigate the pathophysiology of genetic disorders, such as a1antitrypsin deficiency, glycogen storage disease type 1, Crigler-Najjar syndrome, hereditary tyrosinemia type 1, Gaucher disease, Niemann-Pick disease type C and Wilson's disease [14][15][16]20,21].…”
Section: Diseases Models Of Genetic Liver Diseasesmentioning
confidence: 99%
“…Human iPS-Hep cells with genetic modifications may be of value for research into various diseases as described above; however, previous studies also showed that the phenotypes of iPS-Hep cells are immature compared with adult hepatocytes with respect to albumin production, CYP activity and metabolic functions [4,5,18,19]. This problem of the immature nature of iPS-Hep cells as hepatocytes must be resolved.…”
Section: Disease Models Of Liver Fibrosismentioning
confidence: 99%